Industry 4.0 and industrial revolutions: an assessment based on complexity - Pinheiro, Pedro (2019)
The evolution of society can be related to industrial revolutions. Revolutions are disruptive and transformative phenomena that change and interact with several systems. Industrial revolutions depend on changes in scientific, and mostly technological, paradigms and require people’s participation. They are not only created with individual political intentions, because they are collective and complex systems. The expression Industry 4.0, created in Germany in 2011, denotes the so-called fourth industrial revolution. The question considered in this paper is whether Industry 4.0, as the fourth industrial revolution, is effectively underway or is it still only a vision of the future? This article analyses, from the point of view of the science of complexity, the transformations and the relations of industrial systems with other selected systems. It was made through fractal analysis using indicators of four countries, namely, United Kingdom, United States of America, Germany and China. Considering the evolution of population growth, Gross Domestic Product per capita, communication technologies and intellectual property, the results of the analysis show that the factor that stands out is the protection of intellectual property.The analysis of the previous indicators showed that it is not possible to claim that the fourth industrial revolution is underway, implying that Industrial 4.0 may stil be a vision of the future. The results obtained can not be considered conclusive and more research is needed.